Nocturnal excretion of a urinary melatonin metabolite among electric utility workers - Burch, J. B.; Reif, John S.; Yost, M. G.; Keefe, T. J.; Pitrat, C. A. (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'The effects of 60-Hz magnetic field and ambient light exposures on the pineal hormone melatonin were studied among electric utility workers.' ' METHODS ': 'Personal exposure was measured at 15-second intervals over 3 consecutive 24-hour periods. Exposure metrics based on magnetic field intensity, intermittence, or temporal stability were calculated for periods of work, home, and sleep. A rate-of-change metric (RCM) was used to estimate intermittence, and the standardized RCM (RCMS = RCM/standard deviation) was used to evaluate temporal stability. The effects of magnetic field exposure on total overnight 6-hydroxymelatonin sulfate (6-OHMS) excretion and creatinine-adjusted nocturnal 6-OHMS (6-OHMS/cr) concentration were analyzed with adjustment for age, month, and light exposure.' ' RESULTS ': 'Magnetic field intensity, intermittence, or cumulative exposure had little influence on nocturnal 6-OHMS excretion. Residential RCMS magnetic field exposures were associated with lower nocturnal 6-OHMS/cr concentrations. In multivariate statistical analyses, the interaction term for geometric mean and RCMS magnetic field exposures at home was associated with lower nocturnal 6-OHMS/cr and overnight 6-OHMS levels. Modest reductions in the mean 6-OHMS levels occurred after RCMS exposures during work. The greatest reductions occurred when RCMS exposures both at work and at home were combined; therefore the effects of temporally stable magnetic fields may be integrated over a large portion of the day.' ' CONCLUSION ': 'Results from this study provide evidence that temporally stable magnetic field exposures are associated with reduced nocturnal 6-OHMS excretion in humans.
Keywords: 6-hydroxymelatonin sulfate; electromagnetic fields; human; magnetic fields; pineal